Systematic positions and taxonomy of two new ciliates found in China: Euplotes tuffraui sp. nov. and E. shii sp. nov. (Alveolata, Ciliophora, Euplotida). Issue 4 (19th May 2021) - Lian, Chunyu; Wang, Yurui; Jiang, Jiamei; Yuan, Qingxiang; Al-Farraj, Saleh A.; El-Serehy, Hamed A.; Song, Weibo; Stoeck, Thorsten; Shao, Chen
Abstract : The morphology and SSU rDNA-based phylogeny of two small marine euplotid species isolated from China, Euplotes tuffraui sp. nov. and E. shii sp. nov., were investigated. Euplotes tuffraui sp. nov. has a combination of features including body size (35–50 μm × 15–35 μm), body shape (generally triangle-shaped) adoral membranelles gradually bending at rear end, 10 frontoventral, five transverse, two caudal and two closed marginal cirri with the lower one bearing smaller basal plaques, six dorsal kineties with 1–3 and 6–11 dikinetids in leftmost and mid-dorsal kineties, respectively, and dorsal silverline system double- patella -I type. Euplotes shii sp. nov. is a small-sized form (25–35 μm × 15–25 μm) with 10 frontoventral, five transverse, one marginal and two caudal cirri; six or seven dorsal kineties with about seven dikinetids in mid-dorsal kineties and dorsal silverline system double- eurystomus type. Phylogenetic analyses based on molecular data confirmed the branching positions of these new taxa within the genus Euplotes and supported the validity of the two organisms as novel and distinct species.